Prototype Pengembangan Aplikasi Login menggunakan Teknologi Blockchain - Imam Riadi; Herman Herman; Aulyah Zakilah Ifani (Journal of Applied Informatics and Computing, 2021)
The internet is developing so fast, from the kinds of internet technolgy to something that is needed by every user. Information needs and an extensive network system give the easier to access. One of them is wireless, wireless is very helpful for internet users. However, the problem often arises in wireless securing network. Many attacks that make the username and password of the users get hacked. Based on these problems, this study focuses on securing when users login user a device. One of the innovative technologies that be able to solve these problems is Blockchain Technology. By using blockchain technology adversaries will find the difficulty to change and modify the same data on all computers at the same time because it will take the time so long to crack the encryption code on each block of sata on the entire computer network. This study used literature study as a data collection technique. Browsing method using the internet or other network media. This result of this research is the system prototype has been successfully built. The prototype for the development of this login system application has succeed in securing data such as of username and password using blockchain technology. User data is secured and converted into encryption block.